ANALYSIS OF THE QUALITY CONTENT OF TRADITIONAL NYALE PROCESSING (Eunice siciliensis) IN WANUKAKA DISTRICT, WEST SUMBA REGENCY - Suryaningsih Ndahawali; Apliana Kau Pita (Jurnal Perikanan Unram, 2024)
Nyale processing is a typical preparation of the people of Wanukaka District. The process of processing nyale is simple or still traditional, namely by cleaning sea worms obtained from Wanukaka waters and putting them in a clean container (clear jar), then mixing them with salt, basil leaves, squeezed orange juice. Nyale that has been homogenized with additional ingredients is stored at room temperature for the fermentation process. The aim of this research is to determine the organoleptic content, namely color, aroma and taste. The research results have an average value for aroma, namely 2.77 (like), taste with a value of 2.20 (dislike), color with a value of 2.53 (like), so it can be accepted by the majority of panelists. The proximate content is ash content, water content, fat content, protein content, carbohydrate content. The results of the research show that Nyale which is processed traditionally has a water content of 18.37%, ash content of 32.05%, protein content of 8.63%, fat content of 39.01%, carbohydrate content of 1.95%.